Formulation and Specification of Regional Hadith Studies - Assagaf, Ja’far (Diroyah : Jurnal Studi Ilmu Hadis, 2023)
The study of regional hadith is an essential aspect of hadith scholarship but still poses some challenges that need to be addressed to clarify terminology while integrating the concept with Western area studies theory. This article aims to formulate a robust framework for area hadith, focusing on formulation and specification. In this study, the author integrates some of the fundamental theories of hadith science and applies the analysis of the philosophy of al-Tarikh to unpack the stages of regional hadith studies from historical, ideological, and geographical aspects which are linked to the theory of area studies which not only deals with regionalism in particular but critically analyses the roots, the spread of hadith in several geographies and their specifics. The results of this study reveal that regional hadith studies have deep roots, beginning with the discussion on ‘ismah (the impossibility of making mistakes) and the emergence and spread of hadith in Mecca and Medina during the time of the Prophet Muhammad as its formulation. Subsequently, the study expanded to other regions. In addition, it identifies three main specific aspects of regional hadith studies: first, specifications related to the Sanad (chain of narrators), involving narrators from the same or different geographies; second, specifications of narrators based not only on their geographical location but also on their roles and contributions; third, specifications related to the matan (content of the hadith) and its implementation in one or more regions and its relation to certain aspects. This article provides a clear and comprehensive framework for the study of regional hadith, outlining the key elements that should be considered in this research. The findings have significant implications for a deeper understanding of regional hadith, which can enrich hadith science